Callus and hairy root induction of Melaleuca cajuputi Powell - Prangthong, U.; Montri, N.; Saetiew, K. (International Journal of Agricultural Technology, 2020)
It is stated that the lowest percentage of contamination at 49.63% and highest percentage of survival at 37.95% after sterilized with 70% ethanol for 1 min and 1.8 % NaOCl for 30 min. The bud explants were cultured on Murashige and Skoog (MS) medium supplemented with 0, 0.02, 0.04, 0.06, 0.08 mg/l 2,4-Dinitrophenylhylhydrazine (2,4-D) combination with 0, 0.02, 0.04, 0.06, and 0.08 mg/l Thidiazuron (TDZ) for callus induction. The results showed that the explants were cultured on MS medium supplemented with 0.06 mg/l TDZ resulting to be suitable for callus induction with biggest size at 2.56x1.26 cm of width and length. Culturing buds on MS medium supplemented with 0.02 mg/l TDZ had the highest averaged shoot number. The roots were cultured in liquid MS medium supplemented with 0.04 mg/l TDZ, 0.04 mg/l 2.4-D gave the highest weight of hairy roots.